In-Vitro Evaluation of the Anti-Angiogenic Effects of Three Evergreen Plants - Seyedeh Sara Kamyab; Alpana Subodh Moghe*; Sonali Ankush Sawant; Shyam Sunder Nandi (Iranian Society of Pharmacognosy, 2024)
Background and objectives: Inhibition of tumor angiogenesis is a promising strategy employed in the treatment of various cancer types. Its clinical effectiveness is however constrained due to the adverse side effects of antiangiogenic drugs. There is growing interest in the use of medicinal plants for the development of novel drugs with enhanced efficacy. In the present study, we have evaluated three evergreen plants namely, Alstonia scholaris, Polyalthia longifolia, and Terminalia catappa for antiangiogenic properties. Methods: The leaf extracts of the selected plants were investigated for antiproliferative effects on cervical cancer (SiHa) and Human endothelial (HUVEC) cell lines. The anti-angiogenic properties were evaluated in vitro using HUVEC tube formation and cell migration assays, and in vivo using chick chorioallantoic membrane (CAM) assay. They were further assessed for the expression of key angiogenesis-promoting genes HIF1 α, COX-2, VEGFA, and VEGFR2 using quantitative real-time PCR. Results:  The three samples showed significant inhibition of the growth and differentiation of HUVEC cells, as well as the vascularization of CAM layer. Additionally, the extracts displayed a notable down-regulatory effect on the expression of angiogenesis promoter genes. Terminalia catappa demonstrated the highest efficacy in downregulating all genes. Polyalthia longifolia and Alstonia scholaris exhibited selective inhibition of HIF1 α and VEGFA genes, indicating variations in their anti-angiogenesis potential. Conclusion: The study highlighted the remarkable efficacy of Terminalia catappa in inhibiting angiogenesis and its associated genes across multiple pathways. Overall, the study, for the first time, identified the promising potential of three natural candidates for arresting angiogenesis.